2019
DOI: 10.3389/fpsyg.2019.02669
|View full text |Cite
|
Sign up to set email alerts
|

First-Year Students Background and Academic Achievement: The Mediating Role of Student Engagement

Abstract: LR and PR contributed to the conception and the design of the work. LR and PR were responsible for data collection, analysis, and interpretation of data. LR wrote the manuscript with valuable inputs from the remaining authors. JN made important contributions to data analysis. MG and SF made important intellectual contributions to the paper. All authors agreed on all aspects of the work and approved the version to be published.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 64 publications
(87 reference statements)
0
23
0
4
Order By: Relevance
“…It is also possible that students’ engagement played a role in mediating the relationship between background variables and students’ academic achievement as contended by Ribeiro et al (2019). 66 …”
Section: Discussionmentioning
confidence: 99%
“…It is also possible that students’ engagement played a role in mediating the relationship between background variables and students’ academic achievement as contended by Ribeiro et al (2019). 66 …”
Section: Discussionmentioning
confidence: 99%
“…In view of the above, it is indispensable to determine the resources that could be acting as protective factors to avoid early leaving and low academic performance ( Im et al, 2016 , Lombardi et al, 2019 ). Thus, engagement has been established as an indispensable dimension, focused on quality and level of learning, improvement of students’ academic performance, persevering instead of leaving school, and implying their personal and cognitive development ( Kahu, 2013 , Ribeiro et al, 2019 , Rosário et al, 2016 ). In education, engagement is defined as a positive and satisfactory motivational construct, determined by factors such as vigor, dedication and absorption ( Schaufeli and Bakker, 2003 , Schaufeli et al, 2002 ).…”
mentioning
confidence: 99%
“…This percentage is similar to that of other psychology courses (on average 65%) that also incentivize attendance. To some degree at least, this could be seen as an objective indicator of behavioral engagement (Ribeiro et al, 2019;Bond et al, 2020). Previous studies also found SRS use and out-of-class activities to be positively associated with engagement (Heng, 2014;Bond et al, 2020) and, in turn, with achievement (Lei et al, 2018).…”
Section: Discussionmentioning
confidence: 93%
“…These activities are designed to make learning of the course material more effective, with an impact on academic performance. To our knowledge, the effect of such complementary activities on academic performance has yet to be thoroughly examined, although there is some evidence supporting their usefulness ( Heng, 2014 ; Ko et al, 2015 ; Ribeiro et al, 2019 ). For instance, Heng (2014) found a positive contribution of out-of-class educational activities (e.g., time spent on course-related tasks, reading before lectures) to undergraduates’ academic performance, explaining around 20% of the variance in achievement (exam performance).…”
Section: Introductionmentioning
confidence: 99%